A new saproxylic species of Lophocateridae (Coleoptera: Cleroidea) from Upper Cretaceous Kachin amber (Myanmar). (January 2021) - Kolibáč, Jiří; Peris, David
Abstract: Burmacateres longicoxa gen. et sp. nov. is described as the first definite representative of Lophocateridae coming from Cretaceous amber deposits, based on a fossil specimen of Upper Cretaceous Kachin amber, from northern Myanmar. Cleroidea has undergone dramatic taxonomic changes, following the most recent phylogenetic analysis of the group, some of which still need further research and better support. Burmacateres longicoxa gen. et sp. nov. is a well-preserved fossil possessing the appearance and visible morphological features of modern lophocaterids. A saproxylic mode of life, possibly predatory, is inferred for the fossil species, based on similar extant representatives of the family. Highlights: Burmacateres longicoxa gen. et sp. nov. is described as the oldest Lophocateridae. The new species is a fossil from Kachin amber (Myanmar). A saproxylic mode of life, possibly predatory, is inferred for the fossil species.